Influence of Investment Opportunity Set, Effective Tax Rateand Firm Size on Dividend Policy with Liquidity as a Moderation Variable - Lintang Anggi Permatasari (Institute of Computer Science (IOCS), 2021)
This study aimed to analyze empirical evidence about the effect of investment opportunity set, effective tax rate, and firm size on dividend policy with liquidity as a moderating variable. This research uses 90 manufacture company listed at BEI in the periode 2014-2018. The analyze method used is SEM-PLS and sample selection was carried out using purposive sampling method. The results showed the investment opportunity set and firm size have a negative effect on dividend policy. Effective tax rate has a positive effect on dividend policy.Liquidity cannot moderate the effect of investment opportunity set and effective tax rate on dividend policy butliquidity moderate the effect of firm size on dividend policy.